2021
DOI: 10.4064/aa200927-15-2
|View full text |Cite
|
Sign up to set email alerts
|

Linear Diophantine equations in Piatetski-Shapiro sequences

Abstract: Let x denote the integer part of x ∈ R. For a non-integral α > 0, the sequence ( n α ) ∞ n=1 is called the Piatetski-Shapiro sequence with exponent α. Let PS(α) = { n α : n ∈ N}. We say that an equation f (x 1 , . . . , x n ) = 0 is solvable in PS(α) if there are infinitely many pairwise distinct tuples (x 1 , . . . , x n ) ∈ PS(α) n satisfying this equation. In this article, we investigate the solvability in PS(α) of linear Diophantine equations (1.1) ax + by = cz for all fixed a, b, c ∈ N. For example, the s… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
3
1

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 5 publications
0
4
0
Order By: Relevance
“…Hence, we deduce the positivity of the lower limit of #T ≤x (α)/x. This idea comes from the work of Matsusaka and the second author [MS21]. They showed that for any fixed a, b, c ∈ N, there are uncountably many α > 2 such that the linear equation ax + by = cz has infinitely many solutions (x, y, z) ∈ PS(α) 3 .…”
Section: This Corresponds To (21)mentioning
confidence: 99%
“…Hence, we deduce the positivity of the lower limit of #T ≤x (α)/x. This idea comes from the work of Matsusaka and the second author [MS21]. They showed that for any fixed a, b, c ∈ N, there are uncountably many α > 2 such that the linear equation ax + by = cz has infinitely many solutions (x, y, z) ∈ PS(α) 3 .…”
Section: This Corresponds To (21)mentioning
confidence: 99%
“…Hence, we conclude the positiveness of the limit inferior of #T ≤x (α)/x. This idea comes from the work of Matsusaka and the second author [MS21]. They showed that for any fixed a, b, c ∈ N, there are uncountably many α > 2 such that the linear equations ax + by = cz has infinitely many solutions (x, y, z) ∈ PS(α) 3 .…”
Section: This Corresponds To (21)mentioning
confidence: 99%
“…, x k ) = 0. Matsusaka and Saito [10] showed that, for all t > s > 2 and a, b, c ∈ N, the set of all α ∈ [s, t] such that the equation ax + by = cz is solvable, has positive Hausdorff dimension. Glasscock [11] showed that if the equation y = ax + b with real numbers a = 0, 1 and b is solvable in N, then, for Lebesgue-a.e.…”
Section: Introductionmentioning
confidence: 99%